O acolhimento por enfermeiros em UTI: percepções dos familiares - SILVA JUNIOR, Marco Antonio Mesquita da (2019)
INTRODUCTION: For being an environment with intense apprehension, anxiety and fear, the reception in Intensive Care Units (ICU) is one of the main forms of bonding and trust between nurses, patients and their families. As patient and family members feel well hosted, humanization of the service ensures the family's safety regarding the staff they are attending, making hospitalization process less painful and providing a holistic recovery to patients. The ICU, being a hospital sector for critical patients who need specialized and continuous assistance, is often unable to keep the standard expected by family members regarding the reception by the nurse professional due to intense care routine and work overload. OBJECTIVE: This study aimed to describe the perception of family members regarding the nursing care offered by a nurse in a public hospital in the State of Pará. METHODOLOGY: This was an exploratory, observational and descriptive qualitative approach. Twenty patients’ relatives were interviewed in November 2018, following the inclusion criteria: being the relative of a hospitalized patient, over 18 years old, and agreeing to participate in the study by signing The Written Informed Consent Form (WICF). Under age relatives and those who verbally refused were excludes. The data were collected by a semistructured interview, and submitted to thematic analysis. RESULTS AND DISCUSSION: . A large number of visitors were not presented to the unit's nurse (60%), and of those interviewed, 17 (85%) would not be able to identify the nurse among the multidisciplinary team. Three thematic units were used for data analysis: importance of knowing the professional; recognition of the nurse as a source of support in the recovery of health; and relative-nurse bonding, where ignorance by a considerable number of relatives about the real function of the nurse in ICU was found. FINAL CONSIDERATIONS: It can be concluded that the reception has fundamental importance for creating a bond between patients’ family and healthcare team. Thus, research shows that the nurse meeting the family members would develop nursing as a respected, recognized and protagonist profession in ICU care.